Data variables related to wins and losses of game in different scenarios in the WNBA 2023 season - Deng, Y.; Xu, X.; Luo, B.; Lin, F. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The research subarea of sports performance analysis is in constant evolution, with a growing emphasis on the game data analysis. However, available research on womens basketball games is relatively scarce. Therefore, in this paper the author aims to explore the key variables that influence the game outcomes in the Women`s National Basketball Association (WNBA) during the 2023 season. METHODS: Firstly, chi-square tests and k-means clustering to control variables was applied to categorize games into four groups (home balanced, home unbalanced, away balanced, and away unbalanced). Secondly, stepwise regression and logistic regression were employed to identify key variables influencing game outcomes in each group. RESULTS: In the home balanced group 8 variables including field goals made (FG) (+), field goal attempts (FGA) (-), 3-Point field goals made (3P) (+), free throw shooting made (FT) (+), total rebounds (TRB) (+), steals (STL) (+), turnovers (TOV) (-), and personal foul (PF) (-) were identified as key variables. Meanwhile, in the home unbalanced group 6 variables including FG (+), FGA (-), offensive rebounds (ORB) (+), STL (+), blocks (BLK) (+), and TOV (-), similarly away balanced group 8 variables including FG (+), FGA (-), FT (+), TRB (+), assists (AST) (+), STL (+), TOV (-), and PF (-), and in the away unbalanced group 4 variables including 3P (+), offensive rebound percentage (+), defensive rebound percentage (+), and total rebound percentage (+) were identified as key variables. CONCLUSION: The most significant divergence observed occur in the away unbalanced group, while similarities are prominent between home and away balanced groups. Furthermore, these variables encompass both offensive and defensive aspects, contributing to a relatively balanced situation. This research enriches the understanding of the characteristics of key game variables in high-level womens basketball games.